2021
DOI: 10.1111/jbg.12530
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of genome‐wide DNA methylation and gene expression profiles reveals important epigenetic genes related to milk production traits in dairy cattle

Abstract: Epigenetic modification plays a critical role in establishing and maintaining cell differentiation, embryo development, tumorigenesis and many complex diseases. However, little is known about the epigenetic regulatory mechanisms for milk production in dairy cattle. Here, we conducted an epigenome‐wide study, together with gene expression profiles to identify important epigenetic candidate genes related to the milk production traits in dairy cattle. Whole‐genome bisulphite sequencing and RNA sequencing were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Wanting et al . ( 2020 ), compared the transcriptional profiles and genome-wide DNA methylation patterns of cows with highly diverse milk production performances using genome-wide DNA methylation sequencing and RNA-seq on blood tissue, and revealed that blood tissue alterations in DNA methylation and gene expression for the DOCK1, PTK2, and PIK3R1 genes had variations in milk production among cattle. In addition, the quantity of methionine, lysine, choline, and folate in the diet, among other dietary elements that impact milk supply and composition, has been shown by Ana Lesta et al ( 2023 ) to change the methylation status of certain genes in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wanting et al . ( 2020 ), compared the transcriptional profiles and genome-wide DNA methylation patterns of cows with highly diverse milk production performances using genome-wide DNA methylation sequencing and RNA-seq on blood tissue, and revealed that blood tissue alterations in DNA methylation and gene expression for the DOCK1, PTK2, and PIK3R1 genes had variations in milk production among cattle. In addition, the quantity of methionine, lysine, choline, and folate in the diet, among other dietary elements that impact milk supply and composition, has been shown by Ana Lesta et al ( 2023 ) to change the methylation status of certain genes in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“… 2014 and Wanting et al . 2020 ). A considerable number of reports have estimated the methylation status of many candidate genes for their correlation with milk production in different livestock (Pauwels et al 2017 ; Chen et al 2018 ; Zhao et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blood, however, is relatively easy to collect and is responsible for various substance and molecule exchanges with the mammary gland. Moreover, the presence of some immune cells within the blood, such as leukocytes, enables blood transcriptome to reflect the overall physiological condition of cows [16,17]. Therefore, our study used peripheral blood leukocyte transcriptome as a proxy for mammary gland transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood can reflect the physiological conditions of cows as it is responsible for transporting various substances used in milk production [ 12 ]. Some studies have shown that individuals with different milk production performances have different gene expression levels, and potential molecular biomarkers in the blood transcriptome related to milk performance traits have been identified [ 12 , 13 ]. In addition, blood leukocytes are widely used as immune cells in transcriptional surveys of health traits, such as mastitis [ 14 ] and ketosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%